Cyclical theories of social change: Spengler and Toynbee - Kaurin Dragoljub (Sociologija, 2007)
This paper is centrally concerned with discussing critically and rethinking the theoretical concepts put forward by Oswald Spengler in Decline of the West and Arnold Toynbee in A Study of History. It focuses on the theoretical, heuristic and epistemological value of these theories in the era of renaissance of philosophic history in some quarters (see for example Graham, 2002) and cooperation between social sciences. Spengler is credited with the idea of historical cycles, rethinking of the progressivist view and discovering a radically different approach to the study of the human past, which is embodied in his idea of culture as the proper unit for historical and sociological study. However, some of his views proved to be intrinsically intellectually dubious, but on the whole, his was a major contribution to the study of social change. Arnold Toynbee on the other hand was more empirically and sociologically oriented, while Spengler’s views are more heavily philosophical. Toynbee partly developed his ideas rather consistently, but at the same time included many unclear and inaccurate points in his theory. Both authors can be rightfully considered to be classical authors in this field and both provided incentive for studies that cross-cut social sciences (philosophy, history, sociology). Moreover, Decline of the West and A Study of History are truly post-disciplinary works.